2018
DOI: 10.1111/are.13881
|View full text |Cite
|
Sign up to set email alerts
|

Controlling of geosmin and 2‐methylisoborneol induced off‐flavours in recirculating aquaculture system farmed fish—A review

Abstract: Recirculating aquaculture system (RAS) is an increasingly popular alternative to open aquaculture production systems. However, off-flavours and odours can accumulate in the fish flesh from the circulating water and decrease the fish meat quality. Offflavours are typically caused by geosmin (GSM) and 2-methylisoborneol (MIB) that are lipophilic compounds formed as secondary by-products of bacterial metabolism.Even though GSM and MIB are not toxic, they often are disliked by consumers, and both have very low hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 218 publications
(362 reference statements)
1
25
0
Order By: Relevance
“…These conditions are prevalent during the summer months in Israel. Certain cyanobacteria can produce metabolites that cause undesirable flavors to the fish products (Lee et al, 2017; Lindholm-Lehto and Vielma, 2019; Mares et al, 2009; Paerl and Tucker, 1995; Schrader and Dennis, 2005; Tucker and Schrader, 2020), and/or various toxins that can kill both invertebrates and fish (Oberemm et al, 1999; Smith et al, 2008). Over the course of this study, cyanotoxins (microcystins or nodularins) were repeatedly observed in the particulate fraction of the reservoir and the fishponds during summer, at concentrations that, at times, were above the recommended limit for drinking water of 1 µg microcystins L -1 (according to guidelines set by the World Health Organization (WHO, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions are prevalent during the summer months in Israel. Certain cyanobacteria can produce metabolites that cause undesirable flavors to the fish products (Lee et al, 2017; Lindholm-Lehto and Vielma, 2019; Mares et al, 2009; Paerl and Tucker, 1995; Schrader and Dennis, 2005; Tucker and Schrader, 2020), and/or various toxins that can kill both invertebrates and fish (Oberemm et al, 1999; Smith et al, 2008). Over the course of this study, cyanotoxins (microcystins or nodularins) were repeatedly observed in the particulate fraction of the reservoir and the fishponds during summer, at concentrations that, at times, were above the recommended limit for drinking water of 1 µg microcystins L -1 (according to guidelines set by the World Health Organization (WHO, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fish malodor is routinely observed in several cultivated fish species 18 . This problem is frequently associated with the exogenous accumulation of the earthy and musty off-flavors (2-methylisoborneol and geosmin) from water in fish 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…This problem is frequently associated with the exogenous accumulation of the earthy and musty off-flavors (2-methylisoborneol and geosmin) from water in fish 19 , 20 . These compounds' primary producers are species belonging to Actinobacteria and Cyanobacteria phyla 6 8 , 18 , 19 . Recent reports indicated that other species might also contribute to fish malodor (e.g., members of the genera Myxobacteria and Sorangium of the phylum Proteobacteria; 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by selecting phages targeting unwanted contaminants (pathogens or other bacteria), this approach could be used in developing phage-based techniques in managing the RAS biofilter microbiome. For example, geosmin compounds accumulate in fish tissue, causing unwanted earthy taste and odor [27]. Phages infecting geosmin-producing Streptomyces species have already been shown to be capable of reducing geosmin production [28] and could be used in RAS systems to control product quality.…”
Section: Discussionmentioning
confidence: 99%